The SAGE handbook of European foreign policy two volume set - Jørgensen, Knud Erik 1954-; Aarstad, Åsne Kalland; Drieskens, Edith; Laatikainen, Katie Verlin 1965-; Tonra, Ben (SAGE Publications Ltd, 2015)
This reference work is composed of original chapters written specifically to the following themes: research traditions and historical experience; theoretical perspectives; EU actors; state actors; societal actors; the politics of European foreign policy; bilateral relations; relations with multilateral institutions; individual policies; and transnational challenges